Peran Perguruan Tinggi dalam Membentuk Generasi Moderat: Pentingnya Moderasi Beragama bagi Mahasiswa - Jefik Zulfikar Hafizd; Mohamad Rana; Edy Setyawan; Akhmad Shodikin; Ahmad Khoirudin; Tsulis Affah Muntajah; Nurul Ilaina (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study explores the role of higher education institutions in shaping a moderate generation through the internalization of religious moderation values within academic environments. The focus is on the Faculty of Sharia at UIN Siber Syekh Nurjati Cirebon, which implements strategic approaches through an integrative curriculum, participatory teaching methods, and value-based student activities. This research adopts a descriptive qualitative approach using observations and interviews with lecturers teaching courses related to religious moderation. The findings reveal that values such as tolerance, justice, and balance are conveyed through the integration of moderation content in Islamic studies courses, the use of relevant case studies, and open classroom discussions. Students are also engaged in interfaith programs and community service projects that allow them to apply these values in real-life contexts. The study concludes that higher education plays a strategic role in shaping inclusive and tolerant student character. A holistic curriculum and an open academic environment are effective in fostering a moderate generation in a pluralistic society